Targeted inhibition of Pdp1epsilon abolishes the circadian behavior of Drosophila melanogaster. - Lim, C.; Lee, J.; Koo, E.; Choe, J. (Biochemical and Biophysical Research Communications, 2007)
vrille and Par domain protein 1 (Pdp1) epsilon constitute the second transcriptional feedback loop in Drosophila circadian clock system. Their rhythmic expression is controlled by Drosophila Clock (dClk) gene, and they feed back to negatively and positively, respectively, regulate the oscillating transcription from dClk gene. In this study, we characterized the functional domains of PDP1epsilonin vitro using a panel of deletion mutants and showed that PDP1epsilon basic leucine zipper domain can act as a dominant-negative (DN) mutant of wild-type PDP1epsilon. In transgenic flies, the inhibition of PDP1epsilon activity by PDP1(DN) expression or PDP1 knock-down resulted in arrhythmic circadian behavior with altered dorsal projections from small ventral lateral neurons. We propose that one of PDP1-target genes may be involved in the formation of neural connection between the pacemaker cells and their targets for maintaining the rhythmicity of adult locomotor activity under free-running condition.